2005
DOI: 10.1093/eurpub/cki007
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and mortality in Italy

Abstract: In Italy, the relationship between income inequality and health is mixed and not universal, in so far as a positive association was observed only in provinces with lower absolute income. Elderly persons living in Southern Italy represent the population subgroup most vulnerable to unequal income distribution. Income inequality can, in part, explain the historically higher mortality among women in Southern Italy compared to women in the North. These results indicate that income inequality affects the health of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…Level of education also correlates with level of income, which is the basis for measuring socioeconomic position by education or by income. Several recent studies have reported a positive correlation between income inequality and mortality 16,18,20,[23][24] . Mortality rates are higher in populations experiencing highly unequal income distributions (high income inequality) compared to populations with relatively more equal income distributions (low income inequality), regardless of sex.…”
Section: Introductionmentioning
confidence: 99%
“…Level of education also correlates with level of income, which is the basis for measuring socioeconomic position by education or by income. Several recent studies have reported a positive correlation between income inequality and mortality 16,18,20,[23][24] . Mortality rates are higher in populations experiencing highly unequal income distributions (high income inequality) compared to populations with relatively more equal income distributions (low income inequality), regardless of sex.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, another project uses census-based linkage data from the Italian city of Turin (Rosso et al 1997) and more recently the entire Piedmont region (Mamo et al 2005b), but of course, the findings of these studies refer to the local population only. Other investigators attempt to correlate death rates with socio-economic and other indicators, either for the total Italian population (Caselli and Egidi 1981;Caselli and Reale 1999;Materia et al 2005) or for the local population of Rome (Michelozzi et al 1999). This method is inexpensive and easy to apply, but suffers from the weakness typical of so-called 'ecologic analyses', namely, that the aggregate-level relationship between socio-economic status and the mortality of populations in specific areas may be quite different from the individual-level association between these variables (see Valkonen 2006).…”
Section: Introductionmentioning
confidence: 99%
“…People of lower socio-economic profile experience worse health, higher mortality, morbidity and disability rates and are more likely to suffer from certain diseases, cognitive impairment and depression (Anderson and Armstead 1995;Kunst et al 2005;Mackenbach et al 2003;Materia et al 2005). However, the mechanisms through which socio-economic status operates on health are rather unclear.…”
Section: Introductionmentioning
confidence: 99%